Strategic Intelligence Analysis of the Threat of Weapons of Mass Destruction Proliferation: Potential Vulnerability of Indonesia’s National Security - Digna Permata; Broto Wardoyo; David Ronald Tairas (GoAcademica Research & Publishing, 2023)
This study addresses the issue of the proliferation of weapons of mass destruction, which includes the possession of chemical weapons, biological weapons, and nuclear weapons. The international community endeavors to mitigate the dangers posed by the trade in weapons of mass destruction. Changes in technology have contributed to a shift in the sources of funding for weapons of mass destruction. Financial institutions are susceptible to being utilized as a conduit for money laundering and the financing of the proliferation of weapons of mass destruction. There are a variety of transactional options available for money laundering and the financing of weapons of mass destruction by criminals. Financial institutions must therefore adhere to international protocols to prevent the proliferation of weapons of mass destruction. Interviews and documentation studies are used to collect qualitative data for this study.